The Effect of Free Radicals on Vitiligo - Pristia Widya Monica; Nurrachmat Mulianto (HM Publisher, 2023)
Vitiligo is a depigmentation disorder that is commonly found in the community. The causes of vitiligo are multifactorial such as genetic and environmental factors accompanied by the presence of non-specific and specific immune system factors. Melanocytes are the main target exposed by reactive oxygen species (ROS) during the process of melanogenesis. Such exposure can cause loss of homeostasis and cell death and has implications for vitiligo. Clinical manifestations of vitiligo are generally white depigmented macular lesions that are well demarcated. Based on its distribution, vitiligo can be divided into segmental and non-segmental vitiligo different in terms of prognosis, treatment and resolution of vitiligo.